Manejo da mancha-amarela do trigo com rotação de culturas e aplicação de fungicidas em diferentes estádios - Bonini, Cleiton da Luz (2013)
Tan spot caused by Pyrenophora tritici-repentis is one of the most important diseases of wheat in Brazil. The disease causes significant yield losses and its control requires an integrated disease management program. In this research we evaluate the benefits for disease control of crop rotation and fungicide sprays, including applications early at plant tillering. This latter objective was studied in field trials were carried out in Condor-RS (Cotripal experimental field) in 2011 and Passo Fundo-RS (UPF) in 2010 and 2011. All trials were organized as randomized blocks with three or four replicates. Fundacep Horizonte was the cultivar used in Condor while Mirante and Fundacep Raízes were planted in Passo Fundo in 2010 and Mirante and Fundacep Horizonte in 2011. The overall crop management followed technical guidelines for wheat. The fungicides sprays were performed at tillering, elongation, flowering, and early grain filling. The first spray (tillering) in Condor used the fungicides epoxiconazol (Opus 0.6 L.ha-¹), propiconazole (Tilt 0.3 L.ha-¹), tebuconazol (Systemic 0.6 L.ha-¹), epoxiconazole + pyraclostrobin (Opera 0.6 L.ha-¹) and tebuconazol + trifloxystrobin (Nativo 0.6 L.ha-¹); the three following sprays used the mixture of tebuconazol + trifloxystrobin (Nativo 0.6 L.ha-1). The final tan spot severity ranged from 50.5 (propiconazol at tillering) to 87.3% (non-sprayed control). The grain yield varied from 2.672 kg.ha-1 to 2.978 kg.ha-1, but there were no significant differences among treatments. In Passo Fundo, the first fungicide spray at tillering or elongation utilize a triazol (propiconazol 125 g.ha-1, Tilt 0.5 L.ha-1) or a mixture of triazol + strobilurin (epoxyconazol 25g.ha-1 + pyraclostrobin 67.5 g.ha-1, Opera 0.5 L.ha-1, plus the adjuvant Assist 0.5 L.ha-1). All other applications used the later fungicide mixture. Fungicide treatments carried out at tillering did not influence tan spot severity nor grain yield significantly over those initiated at elongation. The severity of tan spot, the grain yield of wheat cultivars, and the disease control with fungicides were also examined under continuous wheat cropping or rotation with oats. Each trial included two wheat cultivars and four spray programs with zero (non-sprayed control), one, two or three applications of epoxyconazol + pyraclostrobin. Tan spot reached maximum leaf severities of 29.6% in 2009, 17.9% in 2010, and 34.5% in 2011. The cultivar Horizonte showed the highest disease severity (34.5% on monoculture/16.1% under rotation), followed by Raízes (29.6%/15.4%), Guamirim (25.7%/11.5%), Mirante (17.9%/6.6% in 2010; 21.2%/8.8% in 2011), and Quartzo (8.8%/5.6%). The average difference in grain yield pro crop rotation varied from 779 kg.ha-1 (2009) to 1.374 kg.ha-1 (2011). Such a difference was higher when combined with two (1.268 kg.ha-1) or three (1.545 kg.ha-1) sprays of fungicide. The net income from fungicide application was R$246.20.ha-1 for two sprays and R$302.49.ha-1 for three. The benefit of the wheat/oat rotation varied among cropping seasons and ranged from R$104.89 to R$564.89 ha-1. In conclusion, crop rotation and fungicide applications initiated at plant elongation provide better management for wheat tan spot